2005
DOI: 10.1038/sj.gt.3302607
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HLA-A2-restricted HPV-16 E7-specific CD8+ T-cell immune responses induced by DNA vaccines in HLA-A2 transgenic mice

Abstract: We have recently demonstrated that linkage of DNAencoding calreticulin to DNA-encoding human papillomavirus-16 E7 antigen strongly enhances the efficacy of DNA vaccines against E7-expressing tumors in animal models. In this study, as a prelude to clinical translation, we characterized the ability of DNA-encoding calreticulin linked to DNAencoding E7 antigen to generate HLA-A2-restricted E7-specific CD8 + T-cell responses in HLA-A2 (AAD) transgenic mice, as well as antitumor effects against an E7 + HLA-A2 + tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 22 publications
2
68
0
Order By: Relevance
“…We observed that the presence of the E7 49-57 aa sequence within the E7 gene of the CRT/E7 DNA vaccine suppresses the efficient activation of HLA-A2 restricted E7 (aa [11][12][13][14][15][16][17][18][19][20] peptide-specific CD8 + T cell-mediated immune responses 13 in HLA-A2 transgenic mice. In order to avoid this situation and accurately characterize the HLA-A2-restricted E7-specific CD8 + T-cell immune response in HLA-A2 transgenic mice, we generated pcDNA3-CRT/ mtE7(del aa49-57), a DNA vaccine that deletes aa49-57 from the E7 gene.…”
Section: Combination Of Hpv E6 and E7 Dna Vaccines S Peng Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the presence of the E7 49-57 aa sequence within the E7 gene of the CRT/E7 DNA vaccine suppresses the efficient activation of HLA-A2 restricted E7 (aa [11][12][13][14][15][16][17][18][19][20] peptide-specific CD8 + T cell-mediated immune responses 13 in HLA-A2 transgenic mice. In order to avoid this situation and accurately characterize the HLA-A2-restricted E7-specific CD8 + T-cell immune response in HLA-A2 transgenic mice, we generated pcDNA3-CRT/ mtE7(del aa49-57), a DNA vaccine that deletes aa49-57 from the E7 gene.…”
Section: Combination Of Hpv E6 and E7 Dna Vaccines S Peng Et Almentioning
confidence: 99%
“…We found that vaccination with pcDNA3-CRT/E7(del aa49-57) generates HLA-A2-restricted E7 (aa11-20) peptide-specific CD8 + T-cell immune response in HLA-A2 transgenic mice. 13 In the current study, we characterized the HLA-A2-restricted E6-and/or E7-specific CD8 + T-cell immune responses generated by vaccination with pcDNA3-CRT/ E6 and/or pcDNA3-CRT/mtE7(del aa49-57) in HLA-A2 transgenic mice by intracellular cytokine staining followed by flow cytometry analysis. As shown in Figure 4, vaccination with pcDNA3-CRT/E6 and pcDNA3-CRT/ mtE7(del aa49-57) generated comparable numbers of HLA-A2-restricted E6 (aa29-38)-specific CD8 + T cells to vaccination with pcDNA3-CRT/E6 without pcDNA3-CRT/mtE7(del aa49-57).…”
Section: Combination Of Hpv E6 and E7 Dna Vaccines S Peng Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, E6 and E7 are ideal immunotherapeutic targets to induce cellular immune responses against HPVtransformed cells (6,7). Significant efforts have been made to develop HPV 16 therapeutic vaccines that target either E6 or E7 proteins (8)(9)(10)(11)(12). However, to date, there have been limited data on HPV 18 therapeutic vaccines.…”
mentioning
confidence: 99%
“…The TC1/A2 line was generated by transforming TC1 cells with HLA-A*0201 from HLA-A*0201 (AAD) transgenic mice. 60 The limitation of this line is that the CD81 T-cell immune response is predominantly directed to against the H-2Db-restricted HPV16 E7 (49-57) epitope in HLA-A*0201 (AAD) transgenic mice. The HLF16 line was generated by transfecting heart lung fibroblasts from HLA-A*0201 transgenic mice with the HPV16 E6 and E7 oncogenes and H-Ras V12.…”
Section: Murine Modelsmentioning
confidence: 99%